Kedudukan Anak Angkat dan Anak Kandung Perempuan dalam Pewarisan Hukum Adat Bali - Nyoman Cintya Putri Wikaryuni; I Nyoman Sujana; Anak Agung Istri Agung (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article analyzes the status of adopted and biological daughters in Balinese customary inheritance law following the 2023 Decree of the Pasamuhan Agung IV of the Balinese Traditional Village Council. The inheritance system remains based on patrilineal descent (purusa), encompassing customary and religious rights and obligations. Adopted children are, in principle, equal to biological children, while daughters are recognized as heirs as long as they have purusa status. The status of ninggal kedaton (retirement from the royal family) affects inheritance rights, except under certain conditions, such as sentana rajeg (retirement from the royal family). This development demonstrates the expansion of recognition of women within the framework of Balinese customary law.